IFN-τ Mediated Control of Bovine Major Histocompatibility Complex Class I Expression and Function via the Regulation of bta-miR-148b/152 in Bovine Endometrial Epithelial Cells - Wu, Haichong; Jiang, Kangfeng; Guo, Shuai; Yang, Jing; Zhao, Gan; Qiu, Changwei; Deng, Ganzhen (Frontiers in Immunology, 2018)
IFN-τ, a type I interferon produced by the trophoblasts of ruminants, has various important immune functions, including effects on the expression of MHC-I. A previous study has reported that IFN-τ promotes the expression of MHC-I molecules on endometrial cells. However, the immunological mechanisms by which IFN-τ regulates MHC-I molecules remain unknown. Here, we investigated which miRNAs may be involved in the regulation of MHC-I molecule expression and function in bovine endometrial epithelial cells. By using TargetScan 6.2 and http: //www.microRNA.org, two miRNAs were suggested to target the 3’UTR of the bovine MHC-I heavy chain: bta-miR-148b and bta-miR-152. Dual luciferase reporter and miRNA mimic/inhibitor assays suggested that bta-miR-148b/152 were negatively correlated with bovine MHC-I heavy chain genes. The function of the MHC-I heavy chain was then investigated using qRT-PCR, ELISA, Western blotting, immunofluorescence and RNA interference assays in primary bovine endometrial epithelial cells (bEECs) and an endometrial epithelial cell line (BEND). The results demonstrated that bta-miR-148b/152 could promote TLR4-triggered inflammatory responses by targeting the bovine MHC-I heavy chain, and the MHC-I molecule negatively regulated TLR4-induced inflammatory reactions may through the Fps-SHP-2 pathway. Our discovery offers novel insight into negative regulation of the TLR4 pathway and elucidates the mechanism by which bovine MHC-I molecules control congenital inflammatory reactions.